Analysis and Modeling of Depletion-Mode MOS Transistors. (1996) - Kumar, Umesh
Abstract : Depletion mode MOSFETs are widely used in MOS—LSI/VLSI circuits as load elements. The main advantages offered by these devices are: Higher packaging density, Improved performance, Reduced power consumption, etc. Masuhara et. al (1972) developed a model for analysis of this device as an enhancement mode MOSFET. The model was adequate for analysis of lightly-doped, shallow-implanted channels. Subsequently, a more rigorous analysis was put forth by HAKEN for larger doping and deep channels. The analysis made by Edward and Marr did not simplify the non-linear relationship between surface depletion region width and gate voltage. The model also did not account for the transconductance of the device in the three operating regimes. In this paper, the various models are briefly examined, and an attempt has been made for extraction of various parameters for obtaining the DC characteristics of these devices.